Orientalism : History, Theory, and the Arts - MacKenzie, John MacDonald (New Delhi Viva Books, 2015)
The Orientalism debate, inspired by the work of Edward Said, has been a major source of cross-disciplinary controversy. This work offers a re-evaluation of this vast literature of Orientalism by a historian of imperalism, giving it a historical perspective.
Include Illustrations, Bibliography and Index.
History, Theory, and the Arts.
Keywords: Arts, Modern -- Orientalism in art -- Exoticism in art